1999
DOI: 10.1016/s0895-7061(99)00123-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of weight loss intervention on antihypertensive medication requirements in the hypertension optimal treatment (HOT) study

Abstract: Obesity is a significant risk factor for hypertension and the cardiovascular sequelae of hypertension. Weight loss has been shown to be effective in lowering blood pressure in overweight individuals. The purpose of this study was to show the impact of a weight loss intervention on overall medication requirements for obese, hypertensive patients. This was a substudy of the Hypertension Optimal Treatment (HOT) study. HOT study patients who had a body mass index > or =27 kg/m2 were randomized to receive either th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(42 citation statements)
references
References 14 publications
1
38
0
3
Order By: Relevance
“…Others could reduce the number and doses of medications. 16 A recent meta-analysis estimated that for every kilogram of weight loss, systolic blood pressure would decrease by 1.05 mm Hg (95% confidence interval: 0.66-1.43) and diastolic blood pressure would decrease by 0.92 mm Hg (95% confidence interval: 0.55-1.28). 17 Although the ultimate responsibility for achieving a healthy weight rests with the patient, the patient's family, clinicians, and others can play major supportive roles.…”
Section: Discussionmentioning
confidence: 99%
“…Others could reduce the number and doses of medications. 16 A recent meta-analysis estimated that for every kilogram of weight loss, systolic blood pressure would decrease by 1.05 mm Hg (95% confidence interval: 0.66-1.43) and diastolic blood pressure would decrease by 0.92 mm Hg (95% confidence interval: 0.55-1.28). 17 Although the ultimate responsibility for achieving a healthy weight rests with the patient, the patient's family, clinicians, and others can play major supportive roles.…”
Section: Discussionmentioning
confidence: 99%
“…17 Persistence of obesity is one of the major reasons for the failure of antihypertensive treatment and for refractory hypertension. 18 Moreover, clinical experience indicates the difficulty in maintaining a long-term weight reduction. 19 Consequently, knowing whether or not genetic background influences changes in body weight, and if this influence is modifiable through antihypertensive treatment, can help in the management of hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In three studies, weight loss was assessed only during a 24-to 48-month induction phase. 53,56,57 Weight loss efficacy. Weight loss was usually o5 kg after 2-3 y (mean (7s.d.…”
Section: Dietary/lifestyle Therapymentioning
confidence: 99%
“…Long-term efficacy of weight loss methods JD Douketis et al Long-term efficacy of weight loss methods Six studies had a 'usual care' control group. 47,[51][52][53]56,59,77 No study reported on weight loss and its effects of cardiovascular risks in high-risk groups, unless the study was limited to high-risk subjects. 47,51,52,56,57,77 Pharmacologic therapy In 19 studies that involved 9953 subjects, the mean age and weight of subjects across studies varied from 40 to 58 y and from 87 to 102 kg (Table 2).…”
Section: Dietary/lifestyle Therapymentioning
confidence: 99%